2019
DOI: 10.22437/ijolte.v3i1.7434
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Passive Voice Occurrence in Scientific Writing

Abstract: This study investigated passive voice use in theses of Graduate EFL students, Universitas Negeri Malang. The occurrences of passive voice in research method chapter in two time periods, 1985 - 2000 and 2002 – 2015 were compared. Passive voice occurrence in chapter of research method was also investigated then it was compared with the active. Passive voice occurrence in theses before 2002 investigated which was 1458, and 1171 in theses published after 2000 indicated the fact that today passive voice use in scie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Their focus was on analyzing the occurrences of active voice (AV) and passive voice (PV) frequencies in research articles for instance, Yannuar et al (2014) analyzed the frequent verbs used in 124 Indonesian undergraduate theses and found that AV appeared more frequently than PV. Similarly, Subagio et al (2019), who investigated the 'Method' section of Graduate EFL students' theses of Universitas Negeri Malang from two periods (1985-2000 and 2002-2015), revealed that AV sentences appeared more frequently in those research reports than PV.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their focus was on analyzing the occurrences of active voice (AV) and passive voice (PV) frequencies in research articles for instance, Yannuar et al (2014) analyzed the frequent verbs used in 124 Indonesian undergraduate theses and found that AV appeared more frequently than PV. Similarly, Subagio et al (2019), who investigated the 'Method' section of Graduate EFL students' theses of Universitas Negeri Malang from two periods (1985-2000 and 2002-2015), revealed that AV sentences appeared more frequently in those research reports than PV.…”
Section: Introductionmentioning
confidence: 99%
“…PV occurrences in students' writing seem to have been underexplored. However, Yannuar (2014) and Subagio (2019) took a different approach compared to the aforementioned studies. Their focus was on analyzing the occurrences of active voice (AV) and passive voice (PV) frequencies in research articles for instance, Yannuar et al (2014) analyzed the frequent verbs used in 124 Indonesian undergraduate theses and found that AV appeared more frequently than PV.…”
Section: Introductionmentioning
confidence: 99%
“…In countries where English is the second language and non-speaking English nations including Indonesia, tend to use passive voice in their research articles and even the passive voice is not only prevalent but heavy-handedly enforced in universities research institutes (Inzunza, 2020). Reconsidering the use of passive in research articles some studies had been conducted by Ahmad, (2012); Subagio et al, (2019) which revealed that the passive voice occurrence is higher than active voice. In line with this statement, Horbowicz et al, (2019); Emeksiz, Erk, (2015), also expressed that passive voices are often taken to be the hallmarks of academic text and traditionally considered to be one of the distinctive features of scientific texts.…”
Section: Introductionmentioning
confidence: 99%